2013
DOI: 10.1039/c3dt50601k
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of diborane(4) by transition metal fragments and a novel metal to π Dewar–Chatt–Duncanson model of back donation

Abstract: The feasibility of using transition metal fragments to stabilize B2H4 in planar configuration by donating 2 electrons to the boron moiety is investigated. Building upon the existing theoretical and experimental data and aided by the isolobal analogy, the model transition metal complexes Cr(CO)4B2H4 (6), Mn(CO)CpB2H4 (7), Fe(CO)3B2H4 (8) and CoCpB2H4 (9) are chosen to illustrate this unique bonding feature--bond strengthening with π-back donation. Other possible types of complexes with B2H4 and the metal fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Several theoretical studies on B 2 H 4 isomers showed that the relative energy difference between various isomers lies below 5.0 kcal mol −1 (Scheme a) . Although such energy differences are small, transition‐metal fragments can be utilized to stabilize these different diborane(4) species …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Several theoretical studies on B 2 H 4 isomers showed that the relative energy difference between various isomers lies below 5.0 kcal mol −1 (Scheme a) . Although such energy differences are small, transition‐metal fragments can be utilized to stabilize these different diborane(4) species …”
Section: Figurementioning
confidence: 99%
“…NBO (natural bonding orbital) analysis showed dissimilar charge distributions around the boron centres (NBO charges: B1=−0.234 and B2=0.134; see Table S2), thus supporting the significantly different 11 B NMR values at −40 °C. This result is also in tune with the computed low barriers for the interconversion of similar B–H–M bridged structures …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In the Li 2 [B n H 3n−2 ] series formed by the consecutive addition of BH 3 to Li 2 BH ( Scheme S6 ), the HDA MeCN values decrease by 20–52 kcal/mol relative to the corresponding neutral boranes B 3 H 3n−2 ( Table 1 and Scheme 2 ). Both [B 2 H 4 ] 2− [ 99 , 102 , 104 , 111 ] and [B 3 H 7 ] 2− [ 82 , 112 , 113 , 114 ] are used as ligands in transition metal complexes. The most stable structures, [B 4 H 12 ] 2− and [B 5 H 15 ] 2− , are based on the geometry of [B 3 H 7 ] 2− , whereas cyclic structures are energetically less favorable by 7.4 and 16.8 kcal/mol (∆G° MeCN ), respectively ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…B2H4 can be obtained by the reaction of B2H6 with F radicals in the gas phase [98]. Due to its high electrophilicity (HDA MeCN = 105.4 for B2H4 is comparable to HDA MeCN = 108.4 for BH3), there is a lack of transition metal complexes with B2H4 [99]; however, it can be stabilized in the form of a Lewis acid-base complex (Me3P)2B2H4 [100][101][102][103][104]. In turn, (Me3P)2B2H4 can act as a bidentate ligand in transition metal complexes [102][103][104][105].…”
Section: Features Of Thermodynamic Hydricity In Homologous Seriesmentioning
confidence: 99%